Empowering translators through entrepreneurship in simulated translation bureaus - van Egdom Gys-Walt; Konttinen Kalle; Vandepitte Sonia; Fernández-Parra María; Loock Rudy; Bindels Joop (Aarhus University, 2022)
This paper reviews entrepreneurial activities that take place within the simulated translation bureaus of member institutions of the INSTB network and establishes a link between entrepreneurism, self-efficacy and perceived competence. Reusing pre-test and post-test data of a student survey, a first attempt is made to design and test a survey instrument for gauging the impact of a simulated translation bureau on perceived entrepreneurial competence and self-efficacy for planning, setting up, and managing a translating organisation in pedagogical translation company simulations. Tentative results suggest a positive effect of participation in translation company simulation modules on students’ entrepreneurial self-efficacy and perceived competence. Because of the anonymity of the data, pre-test and post-test responses could not be paired. As a consequence, the statistical significance of the results could not be confirmed.